Effect of Yoga and Naturopathy intervention on atopic dermatitis: A clinical trial - Mohan, Poorani; S, Prashanth; ST, Venkateswaran (Indian Journal of Integrative Medicine, 2024)
Background: Atopic dermatitis (eczema) is a common chronic or recurrent inflammatory skin disease affects 15–20% of children and 1–3% of adults worldwide. It is characterized by acute flare-ups of eczematous pruritic lesions over dry skin. Yoga and Naturopathy is a safe and cost-effective non pharmacological system which encompassing holistic approach in the prevention and treatment of diseases that is widely used to treat atopic dermatitis. Methods: Various bibliographic databases of previously published peer-reviewed research papers were explored and systematic data culminated in terms of various treatment strategies used for the management of Atopic Dermatitis. The prime focus is given towards system of Yoga and Naturopathy management. Results: A comprehensive review of 15 papers, including both research and review articles, was carried out to make the article readily understandable. The uniqueness, procedure, advantages of Yoga & Naturopathy interventions are discussed in detail. Results showed improvements in EASI and SCORAD scores. This shows the effectiveness of 4 weeks of YN interventions in reducing the severity of Atopic dermatitis. Conclusion: Although there are many modern and alternative treatment strategies available to treat Atopic Dermatitis the Yoga & Naturopathy system have been utilized and found effective; however, their stability and safety become the major impediments towards their successful positioning. This case report suggests that integrated yoga and naturopathy interventions have significant role in managing symptoms of patients with Atopic dermatitis.